The nature of the Late Paleozoic glaciation in Gondwana as determined from an analysis of garnets and other heavy minerals - Gravenor, C. P. (Canadian Journal of Earth Sciences, 1979)
Heavy mineral suites from Late Paleozoic sediments from South Africa, Australia, and Antarctica are dominated by garnet. The enrichment of garnet is attributed to the loss of unstable minerals such as pyroxenes and amphiboles by mechanical abrasion in beach and fluvial environments during periods of deglaciation.An analysis of chattermark trails found on the surface of the garnets shows that the percentage of chattermarked garnets is roughly twice that from samples of Pleistocene glacial sediments of North America. As the percentage of garnets with chattermark trails is a function of the distance of glacial transport, it is concluded that the garnets found in the Late Paleozoic glaciogenic sediments have been transported over very long distances, probably as a result of having been recycled many times. As these glacially mature garnets are found in tillite and other glaciogenic deposits which directly overlie bedrock, it is suggested that much of Gondwana was covered for a long period of time by glaciers of continental dimensions and that much of the record of the early part of the Late Paleozoic glaciation is missing due to glacial erosion.